f(x)= 9x^3+ 2x^2 -5x+ 4
g(x)= 5x^3 -7x+ 4
f(x) - g(x)
= (9x^3+ 2x^2 -5x+ 4) - (5x^3 -7x+ 4)
= 9x^3+ 2x^2 -5x+ 4 -5x^3+ 7x -4
= (9x^3 -5x^3)+ 2x^2+ (7x -5x)+ (4-4) (combine like terms)
= 4x^3+ 2x^2+ 2x
= 2x* (2x^2+ x+ 1)
The final answer is 2x* (2x^2+ x+ 1).
-2x + 8. you multiply all the terms inside the parenthesis by the one outside of/attached to them. the reason it is +8 and not -8 is because the negatives cancel out to give you a positive.
C...................):$;$:$;&::’your welcome
2x9= 18
18×-6= -108
Your answer is 108.